Jerusalem II: Jerusalem in Roman-Byzantine Times - Heyden, Katharina; Lissek, Maria; Kaufmann, Astrid (Civitatum orbis mediterranei studia, 2021)
Cover -- Title -- Preface -- Table of Contents -- Introduction -- Katharina Heyden / Maria Lissek - Jerusalem: Shape, Life and Claims -- Part One. Shape of the City: Topography and Buildings -- Max Küchler / Markus Lau - Topographie und Baugeschichte Jerusalems in römischer und byzantinischer Zeit -- Christoph Markschies - Die Christianisierung Jerusalems und ihre Auswirkungen auf die Urbanisierung -- Ute Verstegen - Die christliche Sakralisierung Jerusalems von Konstantin bis Heraklios -- Harald Buchinger - Liturgy and Topography in Late Antique Jerusalem -- Jürgen Krüger - Die Grabeskirche: Entstehung und Entwicklung bis in frühislamische Zeit -- Part Two. Life in and around the City: Economics and Religions -- Jon Seligman - The Economy of Jerusalem from the second to seventh Centuries -- Ronny Reich - The Cultic and Secular Use of Water in Roman and Byzantine Jerusalem -- Nicole Belayche - The Religious Life at Aelia Capitolina (ex-Jerusalem) in Roman Times (Hadrian to Constantine) -- Hagith Sivan - The Making of Memory : Jerusalem and Palestinian Jewry in Late Antiquity -- Ora Limor - Jewish and Christian Pilgrims to Jerusalem in Late Antiquity -- Andreas Müller - Jerusalem als Zentrum von Wohltätigkeit in der Spätantike -- Brouria Bitton-Ashkelony - Monastic Networks in Byzantine Jerusalem -- Part Three. Claims on the City: Emperors, Bishops and Monks -- Jan Willem Drijvers - Jerusalem - Aelia Capitolina: Imperial Intervention, Patronage and Munificence -- Lorenzo Perrone - Jerusalem als kirchliches Zentrum der frühbyzantinischen Reichskirche -- Christoph Brunhorn - Die Bedeutung Jerusalems für das Mönchtum der Judäischen Wüste: Monastische Topographie im hagiographischen Corpus Kyrills von Skythopolis -- Epilogue. The City in Early Islamic Period -- Angelika Neuwirth - Al-masjid al-aqṣā - The Qur'anic New Jerusalem.